Corrosion inhibition of iron in chloride media by the aqueous extract of curcuma Longa rhizome powder - Abidli, Imen; Nébil Souissi; X. Ramón Novoa (Kuwait Journal of Science, 2021)
The effect of the aqueous extract of Curcuma Longa Rhizome Powder and their main constituents involve phenols compounds, as iron corrosion inhibitor in 0.1 M NaCl solution was tested. Electrochemical impedance spectroscopy (EIS) was employed as the main experimental technique to assess the electrochemical behavior of iron in different concentrations of Curcuma extract. EIS revealed an increase in the charge transfer resistance with increasing inhibitor concentration. The temperature and immersion time effects on the corrosion behavior of iron without and with the extract of Curcuma were also studied. The inhibition action of the extract was discussed in view of the Langmuir adsorption isotherm.